Sistem E-Commerce Berbasis Web pada Perusahaan Batik di Sidoarjo - Deva Martha Shella; Tining Haryanti (FORTEI Regional VII Jawa Timur, 2022)
Batik is an illustrated Indonesian cloth that is specially made by writing or removing wax on the cloth and then processing it in a certain way which has its own characteristics. Batik is one of Indonesia's internationally recognized cultural heritages. Therefore, this raw material is in high demand in most local as well as international markets. It is very important to promote and offer this market in an effective and attractive way. Electronic marketing is the way companies communicate, market and sell products and services via the Internet. However, several batik factories in Indonesia have not implemented this optimally even though they have websites. Interaction with companies is still low, as evidenced by the number of customers who have visited in the last 4 months, around 3,000. They use the batik website only for sightseeing not for shopping. So the purpose of this research is to analyze the level of usability and responsiveness of batik websites in Sidoarjo City batik companies. In this study, a usability test and user experience method were used in which about 30 experienced sources participated. Descriptive statistical analysis was made to clarify the status of the website. The results of this study indicate the ease of use of this current batik standard website is not efficient, and unsatisfactory